Efficiency evaluation of the milling process based on the granulometric analysis of crushed stone-mastic asphalt concrete granulate - D. V. Furmanov; E. S. Budanova (Вестник СибАДИ, 2025)
Introduction. The working process of milling asphalt concrete pavements. The working process of asphalt concrete milling is considered as a set of destruction processes of the stone fraction, bitumen bonds and other phenomena unrelated to the formation of new surfaces. The conducted analysis is based on the assessment of the ratio of energy spent on milling in general and the energy needed for the formation of new surfaces made from separate fractions of asphalt concrete granulate and crushed stone aggregate.Materials and methods. The work is based on carried out experimental studies of the granulometric composition of asphalt concrete granulate obtained by milling crushed stone-mastic asphalt concrete pavement, and, separately, the stone fraction of asphalt concrete got by burning out a bitumen matrix. A standard method was also used to determine the specific energy of destruction of bitumen bonds when determining the fracture disruption resistance of a sample in tension while splitting.Results. As a result of sieving, granulometric curves of the composition of asphalt concrete granulate and stone fraction were obtained. Calculation methods have determined the components of energy consumption for the formation of new surfaces made from asphalt concrete granulate and new surfaces from stone fraction.Discussion and conclusion. At the end of the study, quantitative ratios of various fractions of asphalt concrete granulate of stone-mastic asphalt concrete formed during milling, as well as the crushing grade of stone fractions, were obtained. The specific energy consumption during the milling of asphalt concrete has been determined. It was found that the largest part of the energy during milling (64.7% for this study) is needed for the destruction of bitumen bonds. The vast majority of this energy is used for the formation of the fine granulate fraction. An insignificant part of the energy is spent on the destruction of the stone fraction. In general, the share of energy consumption aimed at the formation of new surfaces accounts for this study 66.14% of the total energy costs. The research development prospects of granulometric analysis for evaluating the effectiveness of the asphalt concrete milling process have been noted.